Want Freedom, Will Travel: Emigrant Self-Selection According to Institutional Quality - Maryam Naghsh Nejad; Andrew T. Young (Institute for the Study of Labor (IZA), 2015)
We investigate emigrant self-selection according to institutional quality using up to 3,566 observations on bilateral migration flows from 77 countries over the 1990-2000 period. We relate these flows to differences in political and economic institutions. We improve and expand upon previous studies by (i) examining decade-long migration flows that (ii) include flows not only to OECD countries but also to non-OECD countries; also (iii) utilizing an estimation method that takes into account the information in zero value migration flows and (iv) examining not only total migration flows but also college-educated and non-college educated subsamples separately. We find that economic freedoms are a significant pull factor for potential migrants. Once economic freedoms are controlled for, measures of political institutions do not enter significantly into our estimations. Results are similar for college- and non-college-educated subsamples. Improvements in legal systems and property rights appear to be the strongest pull factor for potential migrants.
Keywords: O43; F22; P51; 330; emigration; institutions; democracy; economic freedom; brain drain